A Culture of Productivity: Maximizing Productivity by Maximizing Wellbeing - Houck, Brian (ICSE 2022, 2022)
Happy developers are productive developers. Productivity Engineer Brian Houck will share a practitioner’s perspective on how engineering teams across Microsoft are investing in employee wellbeing to make a measurable impact on developer productivity. Measuring developer productivity across multiple dimensions by using a mix of methods, Houck takes a human-centered approach to understanding and maximizing productivity and happiness in his organization. This talk will explore real-world examples of a human centered approach improving the productivity of development teams within Microsoft. How can developers balance their time between collaboration and focused individual work? What impact does social connectedness have on the onboarding of new software engineers? Can more days off actually result in more work getting done? Learn answers to these questions and more!